Blockchain and IoT: The Dynamic Duo Transforming Global Supply Chains - Celestin, Mbonigaba (RIRAI Publisher, 2025)
This research investigates the integration of Blockchain and the Internet of Things (IoT) to transform global supply chains by enhancing transparency, operational efficiency, and security. A qualitative methodology was adopted, combining secondary data analysis, case studies, and expert interviews to explore the applications, challenges, and benefits of these technologies. Major findings revealed that Blockchain reduced fraud by 30% and IoT improved operational efficiency with a 35% reduction in freight tracking delays. The synergistic integration achieved a 27% cost reduction from 2020 to 2024. Despite hurdles such as high initial costs and interoperability challenges, these technologies present immense potential to optimize workflows, enhance real-time monitoring, and promote sustainability in supply chains. Recommendations include investment in scalable frameworks, standardization efforts, and cybersecurity measures to maximize their benefits.